Radiocarbon dating of groundwater from a PZ-2 piezometer located in the foreground of Wieliczka Salt Mine, Poland - Duliński, Marek; Gorczyca, Zbigniew; Marzec, Michał; Czub, Robert; Brudnik, Krzysztof (Geologos, 2019)
A comparison of two methods of radiocarbon age determination of groundwater is presented. The simplest Pearson model and the “user-defined” option of the NETPATH program were considered. Both methods were used to determine the age of water from a PZ-2 piezometer that is situated in the foreground of chamber Z-32 in Wieliczka Salt Mine. Results of these calculations clearly demonstrate that 14C ages obtained by the Pearson model can be significantly overestimated in comparison with those determined by the NETPATH code. Without additional data, such as the stable isotope composition of the water, conclusions on the age of the groundwater based solely on the Pearson model may be highly inadequate.